Answer:
cosФ =
, sinФ =
, tanФ = -8, secФ =
, cscФ =
, cotФ = 
Step-by-step explanation:
If a point (x, y) lies on the terminal side of angle Ф in standard position, then the six trigonometry functions are:
- cosФ =

- sinФ =

- tanФ =

- secФ =

- cscФ =

- cotФ =

- Where r =
(the length of the terminal side from the origin to point (x, y)
- You should find the quadrant of (x, y) to adjust the sign of each function
∵ Point (1, -8) lies on the terminal side of angle Ф in standard position
∵ x is positive and y is negative
→ That means the point lies on the 4th quadrant
∴ Angle Ф is on the 4th quadrant
∵ In the 4th quadrant cosФ and secФ only have positive values
∴ sinФ, secФ, tanФ, and cotФ have negative values
→ let us find r
∵ r = 
∵ x = 1 and y = -8
∴ r = 
→ Use the rules above to find the six trigonometric functions of Ф
∵ cosФ = 
∴ cosФ =
∵ sinФ = 
∴ sinФ = 
∵ tanФ = 
∴ tanФ =
= -8
∵ secФ = 
∴ secФ =
= 
∵ cscФ = 
∴ cscФ = 
∵ cotФ = 
∴ cotФ =
Protons is the answer that makes the most sense
1 Convert 12\frac{2}{3}12
3
2
to improper fraction. Use this rule: a \frac{b}{c}=\frac{ac+b}{c}a
c
b
=
c
ac+b
\frac{12\times 3+2}{3}\times 3\frac{1}{4}
3
12×3+2
×3
4
1
2 Simplify 12\times 312×3 to 3636
\frac{36+2}{3}\times 3\frac{1}{4}
3
36+2
×3
4
1
3 Simplify 36+236+2 to 3838
\frac{38}{3}\times 3\frac{1}{4}
3
38
×3
4
1
4 Convert 3\frac{1}{4}3
4
1
to improper fraction. Use this rule: a \frac{b}{c}=\frac{ac+b}{c}a
c
b
=
c
ac+b
\frac{38}{3}\times \frac{3\times 4+1}{4}
3
38
×
4
3×4+1
5 Simplify 3\times 43×4 to 1212
\frac{38}{3}\times \frac{12+1}{4}
3
38
×
4
12+1
6 Simplify 12+112+1 to 1313
\frac{38}{3}\times \frac{13}{4}
3
38
×
4
13
7 Use this rule: \frac{a}{b}\times \frac{c}{d}=\frac{ac}{bd}
b
a
×
d
c
=
bd
ac
\frac{38\times 13}{3\times 4}
3×4
38×13
8 Simplify 38\times 1338×13 to 494494
\frac{494}{3\times 4}
3×4
494
9 Simplify 3\times 43×4 to 1212
\frac{494}{12}
12
494
10 Simplify
\frac{247}{6}
6
247
11 Convert to mixed fraction
41\frac{1}{6}41
6
1
41 and 1/6
Answer:
P=1
Step-by-step explanation:
1-6=-5
Answer:
True
Step-by-step explanation:
Bcs, in the equation x+(-x)=0 you do x-x ( which is basically x+ -x) and they cancel each other out. This means your equation is 0=0